PENERAPAN MANAJEMEN MUTU SEKOLAH DITINJAU DARI DELAPAN STANDAR PENDIDIKAN NASIONAL SD NEGERI DI KECAMATAN MAKASSAR - Nulaela Bonso; Nawir Rahman; Muh. Yahya (STKIP Pembangunan Indonesia Makassar, 2021)
This study aims 1) to determine the application of quality management in terms of eight educational standards in elementary schools, 2) to determine the supporting factors for the implementation of quality management in elementary schools, 3) to determine the inhibiting factors of quality management in elementary schools. This research is a qualitative research conducted in public elementary schools in Makassar district with the research subjects being the principals and teachers at public elementary schools in Makassar district who are the team for formulating eight National Education Standards in their respective schools. Data was collected by using in-depth interviews, observation, and documentation techniques. The data analysis technique uses descriptive analysis techniques through data reduction, data display and data verification, while the validity of the data uses credibility, time triangulation, transperability, dependability, confirmability. The research results obtained are 1) The implementation of quality management is carried out with four activities, namely planning, organizing, mobilizing, and controlling 2) Supporting factors for the implementation of quality management in schools, namely the leadership of the principal, facilities and infrastructure that are fulfilled and good relations with residents in the school. around school. 3) The inhibiting factors for implementing quality management in schools are teachers who have not mastered 4 skills, namely pedagogic, personality, professional and social. Keywords: Application of quality management